IDENTIFIKASI JENIS ROTAN DI KECAMATAN SELIMBAU KAWASAN TAMAN NASIONAL DANAU SENTARUM - Edi Santoso; . Fahrizal; Hafiz Ardian (Universitas Tanjungpura, 2017)
Forest is a form of ecosystem containing a stretch of land dominated by trees in a natural environment , that cannot be separated ( forestry law about 41). Rattan is one of forest by products growing naturally in the majority of indonesia, forest and was one of the results forest non wood very large role in meeting the needs of people and foreign exchange revenue for the country, so that immediate action is further as identification of rattan in west borneo, especially in the area a national park lake sentarum. The purpose of this research is to identify of rattan ( palmae ) in the lake sentarum national park. Benefits research to provide information about the types contained in selimbau area in a national park lake sentarum to the need for the benefit of operation, preservation, and development. This report is written with uses the method of exploration and a collection of flora cruiser conducted in such a way , in conducting an observation made four lines cruising with long 500 meters while for the distance between the field in accordance with the condition. Fifth the route is track observation A , the observation B , the observation C , and the observation D . A kind of found in domination by the genus Calamus where with a total individual the most ( 4 kind of to 8 individuals ) , in follow by the genus Daemonorops ( two types of with 7 individuals ) , the genus Korthalsia ( three types of to 4 individuals ) , the genus Plectocomiopsis ( two types of with 2 individuals ). Keyword : Danau Sentarum National Park, Identification, Rattan